Resonance Contributions to $η$ Photoproduction on the Nucleon in the Isobaric Model - Burhendi, Feli Cianda Adrin (Omega: Jurnal Fisika dan Pendidikan Fisika, 2017)
The contributions of the resonances $S_{11}(1535)$, $S_{11}(1650)$, and $P_{11}(1710)$ to gamma nucleon $→$ eta nucleon are found. In order to estimate model dependence of the obtained resonance characteristics, an isobaric models used for analysis. For the resonances considered, our analysis yields mass values compatible with those advocated by the Particle Data Group. We emphasise, however, that cross-section data alone are unable to pin down the resonance parameters and it is shown that the beam and or target asymmetries impose more stringent constraints on these parameter values. The amplitude transitions of Feynman diagrams at the center of mass frame used to find amplitude squares involving the s-channel, u-channel, and t-channel on Born term and resonance. The value of the differential cross section on the energy system used by 1.685 MeV up to 2.795 MeV.